PENGARUH LATIHAN PUSH-UP TERHADAP KEKUATAN PUKULAN OI-ZUKI CUDANG PADA ATLET KARATE SHINDOKA CLUB - Dear Lafiesta Sitanggang; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that the arm and shoulder muscle strength of the Shindoka Pekanbaru karate athletes is still weak, this can be seen from various trials and official matches and this is one of the factors causing defeat. This type of research is a type of experimental research to see the effect of the form of exercise. The purpose of this research was to look at the effect of push-up exercises on the strength of the oi-zuki punch in the Shindoka club karate athletes. The population in this research is the Shindoka Pekanbaru club, amounting to 5 people. The sampling technique is to use total sampling, where the total population is sampled. Data collection techniques were obtained from pre-test and post test. The instrument in this study used the Expanding Dynamometer Test as a tool to measure arm and shoulder muscle strength. The analysis was performed using t-test. based on data analysis and discussion, it can be concluded that there is a significant effect of Push-up exercises on the Strength of the oi-zuki cudang punch on Shindoka club karate athletes as evidenced by Tcount of 5,215 and Table 2,132. Means Tcount> Ttabel. At the level ɑ = 0.05. Key Words: Push-Up Exercise, Arm and Shoulder Muscle Strength